Axial tomography in live cell laser microscopy - Richter, Verena; Cremer, Christoph (Journal of biomedical optics, 2017)
Single cell microscopy in a three-dimensional (3-D) environment is reported. Cells are grown in an agarose culture gel, located within microcapillaries and observed from different sides after adaptation of an innovative device for sample rotation. Thus, z -stacks can be recorded by confocal microscopy in different directions and used for illustration in 3-D. This gives additional information, since cells or organelles that appear superimposed in one direction, may be well resolved in another one. The method is tested and validated with single cells expressing a membrane or a mitochondrially associated green fluorescent protein, or cells accumulating fluorescent quantum dots. In addition, axial tomography supports measurements of cellular uptake and distribution of the anticancer drug doxorubicin in the nucleus (2 to 6 h after incubation) or the cytoplasm (24 h). This paper discusses that upon cell rotation an enhanced optical resolution in lateral direction compared to axial direction can be utilized to obtain an improved effective 3-D resolution, which represents an important step toward super-resolution microscopy of living cells.
Gesehen am 01.06.2018